Usefulness of Ultrasound Imaging in Detecting Psoriatic Arthritis of Fingers and Toes in Patients with Psoriasis. (18th January 2011) - De simone, Clara; Caldarola, Giacomo; D'Agostino, Magda; Carbone, Angelo; Guerriero, Cristina; Bonomo, Lorenzo; Amerio, Pierluigi; Magarelli, Nicola
Abstract : Background . Given that clinical evaluation may underestimate the joint damage and that early treatment can slow down psoriatic arthritis (PsA) progression, screening psoriasis patients with imaging tools that can depict early PsA changes would entail clear benefits. Objective . To compare the ability of X-ray and ultrasound (US) examination in detecting morphological abnormalities consistent with early PsA in patients with psoriasis, using rheumatological evaluation as the gold standard for diagnosis. Methods . Patients with chronic plaque psoriasis and no previous PsA diagnosis attending our outpatient dermatology clinic and reporting finger/toe joint and/or tendon pain underwent X-ray and US evaluation; they were subsequently referred to a rheumatologist for clinical examination and review of imaging findings. Results . Abnormal US and/or X-ray findings involving at least one finger and/or toe (joints and/or tendons) were seen in 36/52 patients: 11 had one or more X-ray abnormalities, including erosion, joint space narrowing, new bone formation, periarticular soft tissue swelling, and periarticular osteoporosis; 36 had suspicious changes on US. Conclusion . US proved valuable in detecting joint and/or tendon abnormalities in the fingers and toes of patients with suspicious changes. The dermatologist should consider US to obtain an accurate assessment of suspicious findings.